Spatial dynamics of the lattice Lotka–Volterra competition system in a shifting habitat. (August 2021) - Meng, Yanling; Yu, Zhixian; Zhang, Shengqiang
Abstract: In this paper, we study the spatial dynamics of the lattice Lotka–Volterra competition system in a shifting habitat. First, we discuss the corresponding ranges of the environmental worsening speed c in the following three cases: (a) both species are extinct; (b) one species is extinct, the other is persistent; (c) both species are persistent. Moreover, for species persistence, it is achieved by diffusing to the favorable habitat with certain speeds. Finally, some estimates of these speeds are given.